A Structural Analysis of the Angucycline-Like Antibiotic Auricin from Streptomyces lavendulae Subsp. Lavendulae CCM 3239 Revealed Its High Similarity to Griseusins - Maria Matulova; Lubomira Feckova; Renata Novakova; Erik Mingyar; Dominika Csolleiova; Martina Zduriencikova; Jan Sedlak; Vladimir Patoprsty; Vlasta Sasinkova; Iveta Uhliarikova; Beatrica Sevcikova; Bronislava Rezuchova; et al. (MDPI AG, 2019)
We previously identified the aur1 gene cluster in Streptomyces lavendulae subsp. lavendulae CCM 3239 (formerly Streptomyces aureofaciens CCM 3239), which is responsible for the production of the angucycline-like antibiotic auricin (1). Preliminary characterization of 1 revealed that it possesses an aminodeoxyhexose d-forosamine and is active against Gram-positive bacteria. Here we determined the structure of 1, finding that it possesses intriguing structural features, which distinguish it from other known angucyclines. In addition to d-forosamine, compound 1 also contains a unique, highly oxygenated aglycone similar to those of spiroketal pyranonaphthoquinones griseusins. Like several other griseusins, 1 also undergoes methanolysis and displays modest cytotoxicity against several human tumor cell lines. Moreover, the central core of the aur1 cluster is highly similar to the partial gris gene cluster responsible for the biosynthesis of griseusin A and B in both the nature of the encoded proteins and the gene organization.